Trends and incidence of cartilage, ligament- and arthroscopic surgery: Analysis of German in-patient records 2005-2013. Issue 4 (27th April 2017) - Lodde, Georg; Domnick, Christoph; Herbort, Mirco; Garcia, Patric; Raschke, Michael
Aims and Objectives: Apart from some international cruciate ligament and arthroplasty register data, little epidemiological baseline facts are known about many joint surgical procedures. The German Federal Statistical Office collects the encoded population-based data of all medical in-patient procedures performed in Germany. The purpose of this study was to analyze these data to assess epidemiological trends and incidences in joint surgery. Materials and Methods: The comprehensive database of medical procedures of the German DRG system between 2005 and 2013, including 154 million anonymized in-patient records, were screened and analyzed for joint surgical procedures. Results: Trends of incidence rates of many joint surgical procedures have been detected. There was an increasing incidence of arthroscopic procedures in relation to the open procedures. Anterior cruciate ligament reconstruction or repair has a high incidence of 46 per 100, 000 person-years, most popular grafts were hamstring tendon (90%) and patellar tendon (6.3%) autografts (2013). Conclusion: This is the first baseline epidemiological data out of 154 million in-patient records in Germany including joint and ligament surgical procedures with a focus on knee and shoulder surgery. The knowledge of the trends and incidences of these procedures help to validate and discuss the results of clinical studies and registers.